Pengaruh Perubahan Kurs terhadap Return Saham Sektor Perbankan pada Masa Covid 19 - Sevanya Eunike Lado; Maria Indriyani Hewe Tiwu; Novi Theresia Kiak (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to determine the influence of Covid 19 which has an impact on the depreciation of the rupiah against the US dollar which then has an impact on stock prices. The case study in this research is the share price of the banking sector in the Indonesia Stock Exchange from March 1 to August 31, 2020. The population taken in this research is the banking sector listed on the Indonesian Stock Exchange. The sampling method used purposive sampling so that the number of samples obtained was 4 companies which are state-owned banking companies. Data collection is carried out by documenting data that has been published by the Indonesian Stock Exchange. Investors' reactions to information on the depreciation of the rupiah against the US dollar can be seen from the abnormal stock returns 7 days before and 7 days after information on the depreciation of the rupiah against the US dollar. The method used is the Event Study method with One Sample T-Test and Paired Test data analysis techniques.The conclusion from the results of research and data analysis from 4 state-owned banking companies listed on the Indonesia Stock Exchange during the window period is that it was found that there was no difference in Average Abnormal Return before the depreciation of the rupiah against the United States dollar (event) and after the depreciation of the rupiah against the United States dollar (event). And the paired t-test analysis shows that stock prices before the event do not affect stock prices after the event. This result shows that this market is a semi-strong market according to the Efficiency Market Hypothesis theory.